CERTAIN TYPES OF INSTRUMENTS OF THE ADMINISTRATIVE AND LEGAL MECHANISM FOR ENSURING AIR PROTECTION AND AIRSPACE SAFETY - Gordienko, Artur (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to characterise certain types of instruments of the administrative and legal mechanism for ensuring air protection and airspace security. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain high-quality results. Therefore, the following research methods were used to solve the tasks set: analysis; systematic method; analytical method, etc. Results: one of the most urgent tasks facing Ukraine today is the problem of preserving, improving and restoring the state of atmospheric air, which is favourable for life. Technical regulations play an important role in the protection of atmospheric air. It is indicated that, in accordance with the provisions of the current regulatory legal acts in the field of atmospheric air protection, the main legal mechanisms of state regulation of atmospheric air protection are rationing and standardisation in the field of atmospheric air protection, regulation of the location of facilities and sources of atmospheric air pollution, conducting state environmental and other expert examinations of facilities which have a significant impact on the environment and human health, and the permitting procedure for authorisation by the State of activities which may be accompanied by emissions into the environment. Discussion: the author highlights such instruments as accounting and monitoring of atmospheric air quality and control over the air condition by the state and polluters themselves. These mechanisms and instruments of state regulation allow to protect the atmospheric air from excessive exposure to pollutants and other interference, as well as to carry out state management of the use of atmospheric air.